2014
DOI: 10.1017/s0030605313000689
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of snares in Ruma National Park, Kenya, with implications for management of the roan antelope Hippotragus equinuslangheldi and other wildlife

Abstract: Poaching with snares has been identified as the main cause of decline of the endemic roan antelope Hippotragus equinuslangheldi in Ruma National Park, Kenya, from > 200 in 1979 to 37 in 2009. However, the spatial snaring patterns in the Park are not clearly understood. The focus of our study was to map the spatial distribution of snares in the Park and to identify the factors influencing this distribution, to develop effective methods of wildlife protection. Using data collected from 56 sample plots during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
2
17
1
Order By: Relevance
“…We found that the distribution of risk varied by type of activity. Similar to results in other systems showing an inverse influence of travel distance on illegal behavior (Albers, ; Kimanzi, Sanderson, Rushton, & Mugo, ; Plumptre et al, ; Wato, Wahungu, & Okello, ), we found that distance from the reserve edge was an important factor that influences the risk of all activities. This effect was most pronounced for livestock grazing, which was most common along reserve edges and the most spatially restricted activity.…”
Section: Discussionsupporting
confidence: 82%
“…We found that the distribution of risk varied by type of activity. Similar to results in other systems showing an inverse influence of travel distance on illegal behavior (Albers, ; Kimanzi, Sanderson, Rushton, & Mugo, ; Plumptre et al, ; Wato, Wahungu, & Okello, ), we found that distance from the reserve edge was an important factor that influences the risk of all activities. This effect was most pronounced for livestock grazing, which was most common along reserve edges and the most spatially restricted activity.…”
Section: Discussionsupporting
confidence: 82%
“…We found that 18% of the publications showed evidence of roads facilitating poaching (e.g., Maisels et al, 2013;Shaffer and Bishop, 2016). These studies were specifically in East (e.g., Jones et al, 2009;Kimanzi et al, 2015) and Central Africa (e.g., Wilkie et al, 2000;Haurez et al, 2013), and they primarily focused on mammals, such as the African elephant (Maingi et al, 2012;Shaffer and Bishop, 2016), forest elephant (Blake et al, 2007;Maisels et al, 2013), Western Lowland gorilla (Stokes et al, 2010;Haurez et al, 2013) and Temminck's ground pangolin (Smutsia temminckii, Pietersen et al, 2011). With many of these species classified as threatened (IUCN, 2018a), and with annual estimates of the cost of wildlife crime ranging from US$10-20 billion globally (Wilson-Wilde, 2010), the effort of research undertaken, specifically in these regions, supports the need for an understanding of both habitat and species of concern.…”
Section: Quality Of Evidencementioning
confidence: 79%
“…Threats faced by various subpopulations of roan antelope, the majority of which were documented in southern Africa, include predation (McLoughlin & Owen‐Smith ), poaching (Kimanzi et al. ), habitat loss and deterioration, competition from other grazers and livestock, diseases, human settlement, the erection of veterinary fences and agricultural encroachment, low rainfall, extreme droughts, fires, floods, and inbreeding (Grant & Van der Walt , Martin , Waltert et al. , Kimanzi & Wanyingi ).…”
Section: Resultsmentioning
confidence: 99%
“…Threats to roan antelope populations in the rest of Africa have not been comprehensively assessed in recent times (Poché 1974, Allsopp 1979, Beudels et al 1992, Martin 2003, Kimanzi & Wanyingi 2014. Threats faced by various subpopulations of roan antelope, the majority of which were documented in southern Africa, include predation (McLoughlin & Owen-Smith 2003), poaching (Kimanzi et al 2015), habitat loss and deterioration, competition from other grazers and livestock, diseases, human settlement, the erection of veterinary fences and agricultural encroachment, low rainfall, extreme droughts, fires, floods, and inbreeding (Grant & Van der Walt 2000, Martin 2003, Waltert et al 2009, Kimanzi & Wanyingi 2014. The effects of these pressures on roan antelope survival appear to be locally variable, and roan antelope populations seem to be declining at an unprecedented rate (Kimanzi & Wanyingi 2014).…”
Section: Threats To Populationsmentioning
confidence: 99%